2022
DOI: 10.1038/s41533-022-00283-x
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer and Covid-19: lessons learnt from the pandemic and where do we go from here?

Abstract: The Covid-19 pandemic has significantly disrupted all aspects of healthcare, and while the worst may be over, its broader impact on health services, such as cancer diagnosis and treatment, is likely to be profound. We examine, in this paper, how our response to Covid-19 impacted on the recognition, referral, and diagnosis of individuals with lung cancer in primary care. The overlapping nature of symptoms of Covid-19 and lung cancer posed a particular challenge, and lung cancer referrals have been slow to retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…43,44 In Northern Ireland pathologically diagnosed lung cancer cases have been particularly slow in returning to pre-pandemic levels, while deficits in lung cancer referrals from GPs in the United Kingdom remain. 42,45 Severe access restrictions and reduced attendance at dentists and dental services due to pandemic are likely contributory factors to both the later stage at diagnosis and poorer survival of HAN cancer patients found in our study. Indeed, the dramatic reduction in dental visits in Northern Ireland at the start of the pandemic has not recovered, which is concerning as regular dental visits have been shown to be associated with earlier stage of diagnosis for oral and pharyngeal cancers and dentists have been acknowledged as key to management of patients treated for head and neck cancer.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…43,44 In Northern Ireland pathologically diagnosed lung cancer cases have been particularly slow in returning to pre-pandemic levels, while deficits in lung cancer referrals from GPs in the United Kingdom remain. 42,45 Severe access restrictions and reduced attendance at dentists and dental services due to pandemic are likely contributory factors to both the later stage at diagnosis and poorer survival of HAN cancer patients found in our study. Indeed, the dramatic reduction in dental visits in Northern Ireland at the start of the pandemic has not recovered, which is concerning as regular dental visits have been shown to be associated with earlier stage of diagnosis for oral and pharyngeal cancers and dentists have been acknowledged as key to management of patients treated for head and neck cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Reduced 1‐year survival for all cancers overall was driven by five tumours; Lung Head and Neck, Oesophageal, Lymphoma and Uterine cancer. Regarding lung cancer, the similarity and overlap of symptoms with COVID‐19 have created particular challenges, with individuals with a new cough and breathlessness advised to isolate and test for COVID‐19, which may have led to delayed or missed diagnoses 42 . Indeed, a study reported that people avoided healthcare services despite having concerning symptoms, or if they felt COVID‐19 was the cause of their symptoms, while another reported reduction in people presenting with cough to primary care in 2020 43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly with delays and discontinuation of treatment, various studies have also revealed a hesitancy by cancer patients to consult and visit hospitals for non-COVID-19 issues during the pandemic [ 20 , 21 ]. The observed reduction in the number of consultations for cancer symptoms in primary care during the pandemic may further lead to more advanced cases of lung cancer that unfortunately will not be eligible for surgical treatment [ 22 , 23 ]. Finally, another critical consequence is the temporary discontinuation of screening programs for cancer that has contributed to a significant decrease in the incidence of new cancer cases [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…случаях рака ободочной кишки (С18), ректосигмоидного соединения и прямой кишки (С19-20), трахеи, бронхов и легкого (С33-34), молочной железы (С50), шейки матки (С53), тела матки (С54), яичников (С56-57), предстательной железы (С61) и почки (С64) для анализа были получены в деперсонифицированном виде из базы данных АОКР. В данные включались: идентификационный номер, пол, дата рождения, дата установления диагноза, топография и морфология по Международной классификации болезней для онкологии 3 пересмотра, 1 версии (МКБО-3.1), стадии по классификации UICC/AJCC TNM 8 версии (2017) [20]. Снижение на 15 % и более числа новых случаев было равномерным для всех стадий и возрастных групп скрининга в нашем исследовании при колоректальном раке.…”
Section: материал и методыunclassified